Alpha‐lipoic acid reduces methylmercury‐induced neuronal injury in rat cerebral cortex via antioxidation pathways. Issue 3 (14th June 2016) - Yang, Tianyao; Xu, Zhaofa; Liu, Wei; Feng, Shu; Li, Hongpeng; Guo, Meixin; Deng, Yu; Xu, Bin
ABSTRACT: Methylmercury (MeHg), an extremely dangerous environmental pollutant, accumulating preferentially in central nervous system, causes a series of cytotoxic effects. The present study explored the mechanisms which contribute to MeHg‐induced neurotoxicity focusing on the oxidative stress in rat cerebral cortex. In addition, the protective effects of alpha‐lipoic acid (LA), a potent antioxidant on MeHg‐mediated neuronal injury, was also investigated in current study. A MeHg poisoning model was established as 64 rats randomly divided into 4 groups of which saline control group, MeHg‐treated groups (4 and 12 μmol kg −1 ), and LA pretreatment (35 μmol kg −1 ) group, respectively. After administration of 12 μmol kg −1 MeHg for 4 weeks, it was found that obvious pathological changes and apoptosis in neuronal cells. Meanwhile, total Hg levels elevated significantly, superoxide dismutase (SOD) and gluthathione peroxidase (GSH‐Px) activities were inhibited, and ROS formation elevated, which might be critical to aggravate oxidative stress in cerebral cortex. In addition, NF‐E2‐related factor 2 (Nrf2) pathways were activated, as heme oxygenase‐1 (HO‐1) and γ‐glutamylcysteine synthetase heavy subunit (γ‐GCSh) expressions were up‐regulated obviously by MeHg exposure. Moreover, activities of Na + ‐K + ‐ATPase and Ca 2+ ‐ATPase were inhibited, leading to intracellular calcium (Ca 2+ ) overload. LA pre‐treatment partially reduced MeHg neurotoxic effects via anti‐oxidation pathways. In conclusion, these findings clearly indicated that MeHg aggravated oxidative stress and Ca 2+ overload in cerebral cortex. LA possesses the ability to prevent MeHg neurotoxicity through its anti‐oxidative properties. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 931–943, 2017.